2000
DOI: 10.1007/s00223001089
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Randomized Trials of the Effect of Exercise on Bone Mass in Pre- and Postmenopausal Women

Abstract: Studies of the effect of exercise programs on bone mass appear inconsistent. Our objective was to systematically review and meta-analyze randomized trials of the effect of exercise on bone mass in pre- and postmenopausal women. A computerized MEDLINE search was conducted for the years 1966-1997. Thirty-five randomized trials were identified. Meta-analytic methods were used to statistically pool results of studies of the effect of impact (e.g., aerobics) and non-impact (e.g., weight training) exercise on the lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
195
0
9

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 384 publications
(212 citation statements)
references
References 42 publications
8
195
0
9
Order By: Relevance
“…Hypothetically, GRF values would double if only one leg supported the weight of the whole body, as happens during a hop, as opposed to body weight being distributed on two legs, as is (66) . †Wallace & Cumming (52) . ‡Wolff et al (67) §Kelley & Kelley (68) .…”
Section: Longitudinal Unilateral Studiesmentioning
confidence: 99%
“…Hypothetically, GRF values would double if only one leg supported the weight of the whole body, as happens during a hop, as opposed to body weight being distributed on two legs, as is (66) . †Wallace & Cumming (52) . ‡Wolff et al (67) §Kelley & Kelley (68) .…”
Section: Longitudinal Unilateral Studiesmentioning
confidence: 99%
“…PA and calcium intake have been shown to be beneficial in terms of DXA-derived BMD, (12,13,16,17) but their role in modulating the compensatory adaptation that attempts to maintain the mechanical competence of bone structure is not known. Therefore, the purpose of this cross-sectional study was to examine associations of PA and calcium intake with the volumetric bone density and size of non-weight-bearing radius and weight-bearing tibia among healthy pre-and postmenopausal women.…”
mentioning
confidence: 99%
“…Since a systematic review of randomized trials showed that both impact and non-impact exercise have a positive effect on BMD at the lumbar spine in preand postmenopausal women [20], and exercise such as volley ball, swimming, walking and tennis was significantly associated with high bone mass in the present study (unpublished observation), there might be differing effects of exercise on BMD and fracture. Although details of this discrepancy between BMD and fracture were obscure, it is quite likely that exercise is linked to accidental falls, a risk of fracture.…”
Section: Outcome Assessmentmentioning
confidence: 59%